The role of ATF3 in precision medicine of brain arteriovenous malformation: based on endothelial cell proliferation - Ma, Jiwei; Meng, Lei; Ji, Jiyu; Wang, Xiangyang; Wu, Nan; Sun, Lei; Zhao, Shupeng (Frontiers in Immunology, 2025)
BackgroundBrain arteriovenous malformation (BAVM) is a destructive high-flow vascular abnormality that can lead to various cerebral hemodynamic disorders. The incidence of BAVM has risen significantly in recent years, yet treatment options remain limited. Endothelial cells (ECs) have been proved to be one of the key factors leading to abnormal cerebrovascular structure. Therefore, it is important to explore the pathogenesis of the disease and develop new treatment strategies. With the rapid advancement of single-cell sequencing (scRNA-seq) and the integration of multi-omics data offers a novel perspective for precision medicine.MethodsWe first analyzed scRNA-seq data from the GEO database. We used monocle2, CytoTRACE, and slingshot to perform pseudotime trajectory analysis on ECs. CellChat was used to analyze cell-cell communication in BAVM, and pySCENIC was used to analyze related transcription factors (TFs). Finally, transfection, CCK-8, RT-qPCR, Transwell, EdU, tube formation, and other commonly used experiments were conducted to further validate the effects of key TFs on ECs intervention.ResultsscRNA-seq analysis showed that ECs in BAVM had significant specificity. C0 subpopulation was the key subpopulation, showing strong proliferation and differentiation ability. This study emphasized that the midkine(MK, MDK)signaling pathway was a significant signaling pathway. Heparin-binding growth factor midkine was a secreted protein with a molecular weight of 13 kDa. Studies had shown that it can promote endothelial cell proliferation and lead to angiogenesis. Then, the C0 subpopulation was also associated with a variety of TFs, among which ATF3 played a key role in the pathogenesis of BAVM. The possibility of ATF3 affecting the progression of BAVM was verified by cell experiments.ConclusionThis study employed scRNA-seq and multi-omics analysis to elucidate the pathogenesis of BAVM, uncovering the key role of ATF3 in ECs proliferation. Targeting ATF3 provided a new possibility for the treatment of BAVM and also made up for the blank of ATF3 in the exploration of BAVM. This study provided a theoretical basis for the personalized treatment of BAVM and demonstrated the potential of scRNA-seq and multi-omics methods in advancing precision medicine.